On the formation of intermetallic matrix composites produced by mechanical alloying and sputtering - Neves, F. (2007)
(Ti-48Al)-based intermetallics were synthesized by a combination of mechanical alloying, sputtering and hot isostatic pressure techniques. Blended elemental powders of TiH2 and Al with nominal composition TiH2-48Al were mechanically alloyed for different periods of time. The powders were then coated with Ti and Ag and subsequently hot isostatically pressed at 900 °C with a maximum pressure of 150 MPa for 2 h. Finally they were heat treated at 1200 °C for 4 h. After processing, the compacts obtained from the TiH2-48Al coated powders had a lower hardness but a higher Young's modulus and fracture-toughness than the uncoated compacts. Therefore, the combined used of mechanical alloying, sputtering and compaction techniques might be an alternative method for the synthesis of compacts with non-conventional microstructures, formed by surface modified intermetallic particles.